Development of a bamboo hollower mechanism / Muhammad Arsyad Anuar - Anuar, Muhammad Arsyad (2023)
In this current era, people still using many furniture and tools from bamboo tree especially Lemang seller where the bamboo is used as the utensils to cook Lemang and there is not many tools or mechanism which can help the seller to cut the inside of the bamboo tree and make it hollow which is why this mechanism is being made to help solve this problem and also can cut the bamboo easily where this mechanism will be drilling the center of the bamboo without anyone holding it and the bamboo can be cut safely without any risk of injury and can be cut cleanly. Bamboo plant is a plant used for different purposes which include furniture, decoration, and food preparation. In food industry, bamboo is used as a casing for lemang. The lemang sellers need to cut the bamboo according to the required length and clean the inner part of the bamboo manually before filling them with rice and coconut milk. This project focuses on the development of a bamboo hollower that cuts and clear the inner part of the bamboo. The products use a rotational mechanism by the use of a sprocket. This product helps minimizes the amount of work and time required to clean the bamboo thus increasing the productivity. This product is beneficial for the lemang sellers and other industries that utilized bamboo as the main material